Voicing Suggestions and Enabling Reflection: Results of an Expert Discussion on Proactive Assistants for Time Management - Jeromela, Jovan; Conlan, Owen (Association for Computing MachineryNew YorkNYUnited States, 2023)
While voice-controllable Intelligent Personal Assistants (IPAs) have become widespread in recent years, they remain primarily reactive with rather constrained calendaring capabilities. Anticipating more adaptive and complex assistants in the future, we organised a multidisciplinary expert discussion investigating potential use cases, interaction principles, and user modelling challenges within proactive IPAs for time management. This paper presents the identified themes and deliberations on enticing self-reflection, longitudinal task assistance, interaction modality, dialogue design, perception of the system, usage willingness, onboarding, and explainability. These findings outline a framework of advanced IPAs for time management.
The 5th International Conference on Conversational User Interfaces
PUBLISHED
Poster paper
Eindhoven, The Netherlands
Keywords: Adaptation; Context; Data representation; Personalisation; Control; Time management; Digital Engagement; Artificial Intelligence; Human computer interactions; Ubiquitous Computing